2016
DOI: 10.1080/08946566.2016.1185985
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of elder abuse and neglect among health care professionals in Malaysia: An exploratory survey

Abstract: Elder abuse and neglect (EAN) is a hidden public health challenge for Malaysia. This cross-sectional survey studied the awareness of EAN among 148 doctors and nurses from two neighboring states in Malaysia using a self-administered questionnaire exploring their knowledge, perceptions, practices, and experience concerning EAN. Both doctors and nurses demonstrated poor understanding of signs of EAN and exhibited misperceptions on reporting requirements. Both groups perceived EAN as a national burden and reportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 15 publications
2
18
0
5
Order By: Relevance
“…We can conclude that university education and/or participation in various forms of postgraduate training allow to gain knowledge and skills necessary to implement prevention of domestic violence. Results of this study correspond to results obtained by other authors [1,14,15,16] who not only confirm a relationship between the level of education of nurses and their knowledge of domestic violence (i.e. forms, symptoms, tools necessary to implement prevention), but also point out that education and information support, provided to health care personnel, are the grounds for their effective intervention and proper identification of violence against elders.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We can conclude that university education and/or participation in various forms of postgraduate training allow to gain knowledge and skills necessary to implement prevention of domestic violence. Results of this study correspond to results obtained by other authors [1,14,15,16] who not only confirm a relationship between the level of education of nurses and their knowledge of domestic violence (i.e. forms, symptoms, tools necessary to implement prevention), but also point out that education and information support, provided to health care personnel, are the grounds for their effective intervention and proper identification of violence against elders.…”
Section: Discussionsupporting
confidence: 90%
“…Można zaryzykować twierdzenie, że wykształcenie wyższe i/ lub uczestniczenie w formach kształcenia podyplomowego przekłada się na wiedzę i umiejętności niezbędne do realizowania profilaktyki przemocy domowej. Rezultaty niniejszego badania są zbieżne z wynikami autorów polskich [1,14,15,16], którzy Ryc. 1.…”
Section: Dyskusjaunclassified
“…Physicians have an important role in determining the findings of abuse and neglect, reporting suspected cases and discovering barriers and supports in the detection and management of elder abuse cases (6,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies investigated the level of knowledge, attitudes and behaviors towards NAE, and it was understood that there are many missing points in the diagnosis of NAE and how to act on the subject. In these studies, the participants reported that they had not received adequate and effective training [17,[27][28][29][30][31]. In our study, 81.2% of the participants stated that they were trained about the subject; however, 71% of them did not follow the up-to-date developments in the field.…”
Section: Discussionmentioning
confidence: 57%